THE IMPACT OF THE INDUSTRIAL REVOLUTION ON THE OTTOMAN ECONOMY AND ITS REFLECTIONS ON THE ECONOMIC POLICIES OF THE REPUBLIC PERIOD (1876-1938) - Bahattin KELEŞ (Fırat University, 2021)
The industrial revolution, emerged in England in the eighteenth century and affected the neighbouring countries since the first half of the nineteenth century, greatly affected the countries with non-developed industries. The industrial revolution, emerged in Europe strongly demonstrated the existence of a trade flow from the centre to the periphery, and it first began to affect the Ottoman Empire, India and China. The Ottoman Empire could not keep up with this industrial revolution and upon the Treaty of Balta Limani, signed with England in 1838, it became an open market for European countries. The European countries, which started mass production with the industrial revolution and produced the products that they produced cheaply, were selling these goods with very low customs in the Ottoman country and earning great revenues. Although the Ottoman enacted the Law for the Encouragement of Industry over time, this decline and collapse continued due to reasons such as the ongoing management of the manufacturing industry with classical methods, lack of qualified personnel and low quality in production. When Atatürk founded the Republic, he attached great importance to industrialization in order to further improve the economic structure that he took over from the Ottoman Empire. The private sector was supported, even partially, with the industrial policies implemented in the Atatürk period. By the Izmir Economy Congress held in 1923, new breakthroughs and targets in the economy were determined and the way for economic development was paved by working accordingly. New factories were established in many parts of the country and the support of the private sector was also sought.